2016
DOI: 10.1177/1359104516635221
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of Neuro-Physiological Psychotherapy: An integrative therapeutic approach to working with adopted children who have experienced early life trauma

Abstract: Research into the effectiveness of therapeutic interventions for older children who have experienced multiple forms of trauma within the context of their early development is scant. This article explores the effectiveness of Neuro-Physiological Psychotherapy (NPP): a wrap-around multi-disciplinary, neuro-sequential, attachment-focussed intervention for children and families who present with multiple, clinically significant, emotional and behavioural difficulties. In total, 31 young people and their adoptive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Studies on Dialectical Behaviour Therapy (DBT) have shown that it significantly improves emotional functioning, with positive outcomes in areas such as self-harm, relational difficulties, and substance abuse [24]. Similarly, the application of the Attachment, Regulation, Competency (ARC) model has been found to enhance behavioural and emotional regulation in children [25].…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…Studies on Dialectical Behaviour Therapy (DBT) have shown that it significantly improves emotional functioning, with positive outcomes in areas such as self-harm, relational difficulties, and substance abuse [24]. Similarly, the application of the Attachment, Regulation, Competency (ARC) model has been found to enhance behavioural and emotional regulation in children [25].…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…This has led researchers such as Tarren-Sweeney (2010) to argue that these children do not access the correct services sufficiently because they are not well enough understood and to develop alternative ways of conceptualising the range of issues that such children have. McCullough et al (2014McCullough et al ( , 2016 researched looked-after children with a diagnosis of ASD. They were given a battery of tests including the Autistic Spectrum Quotient and tests of theory of mind abilities.…”
Section: Complex Nature-nurture Interactionsmentioning
confidence: 99%
“…It is essential that the NPP model, like any other, is able to evidence its efficacy. This process has begun and an evaluation of NPP exploring treatment outcomes is presented in a companion paper (McCullough, Gordon-Jones, Last, Vaughan, & Burnell, this issue).…”
Section: Moving Towards Practice-based Evidencementioning
confidence: 99%